Microscopical Indices Of Thymus in Newborn Fetuses - Khusanov Erkin Uktamovich; Korzhavov Sherali Oblakulovich; Miniyarova Alyona Rustamovna (Genius Journals, 2022)
The formation of the immune system in ontogenesis, in particular its central organ, the thymus, is determined by a set of relationships between mother and fetus and the course of the offspring's early adaptation to the conditions outside utero. As a rule, in early postnatal ontogenesis the immune system is in a transient state and continues to form under the influence of a variety of external factors. An uncomplicated pregnancy largely determines the normal course of maternal-fetal immunological relations and determines the development of a complete immune system and its central and peripheral organs in the offspring in postnatal ontogenesis.
Keywords: newborn; thymus; thymus gland; thymus anatomy